05 ANALISIS PENDAPATAN PABRIK PENGGILINGAN PADI (Studi Kasus Penggilingan Padi Di Kelurahan Pabundukang, Kecamatan Pangkaje’ne, Kabupaten Pangkep) - Jurnal Agribis; Muhammad Iqbal; Mohammad Anwar Sadat; Arifin Arifin (Universitas Muslim Maros, 2020)
This research was conducted on Jalan Keadilan, Pabundukang Village, Pangkajene District, Pangkep Regency. This location was chosen with the consideration that it has been a long time running rice mill business. There are two data used, namely: data Primary data is data obtained or taken directly on the object of research, namely at the Haeruddin Rice Mill and secondary data is data obtained from various government agencies related to this research and various other literature as support in preparing the results of this study. The purpose of this study were: to analyze the income and feasibility of the Haeruddin Rice Mill business on Jl. Justice Ex. Pabundukang Kec. Pangkaje'ne Kab. Pangkep. This study uses a quantitative descriptive analysis method to determine the amount of income obtained by farmers from Haeruddin rice milling business on Jl. Justice Ex. Pabundukang Kec. Pangkaje'ne Kab. Pangkep. The results of this study indicate that the income of Haeruddin rice milling business in the last five years has fluctuated. In 2015, he earned an income of Rp. 145,694,763, in 2016 increased to Rp. 179,985,499, in 2017 Haeruddin's rice mill business revenue still increased to Rp. 211,695,587, but in 2018 operating income has decreased from the previous year which amounted to Rp. 109,183,316, and in 2019 Haeruddin's rice mill business income again increased by Rp. 113,723,985. Haeruddin rice milling business is eligible for business with an R / C ratio value from 2015-2019, namely > 1.